Dialkyl Carbonates in the Green Synthesis of Heterocycles - Tundo, Pietro; Musolino, Manuele; Aricò, Fabio (Frontiers in Chemistry, 2019)
This review focuses on the use of dialkyl carbonates (DACs) as green reagents and solvents for the synthesis of several 5- and 6-membered heterocycles including: tetrahydrofuran and furan systems, pyrrolidines, indolines, isoindolines, 1,4-dioxanes, piperidines and cyclic carbamates. Depending on the heterocycle investigated, the synthetic approach used was different. Tetrahydrofuran systems, pyrrolidines, indolines, isoindoline and 1,4-dioxanes were synthetized using dimethyl carbonate (DMC) as sacrificial molecule (BAc2/BAl2 mechanism). Cyclic carbamates, namely 1,3-oxazin-2-ones, were prepared employing DACs as carbonylating agents, either by BAc2/BAl2 mechanism or through a double BAc2 mechanism. Piperidines were synthetized taking advantage of the anchimeric effect of a new family of dialkyl carbonates, i.e., mustard carbonates. Finally, in the case 5-hydroxymethylfurfural (HMF), DMC has been employed as efficient extracting solvent of this extensively investigated bio-based platform chemical from the reaction mixture. These synthetic approaches demonstrate, once again, the great versatility of DACs and their – yet to be fully explored – potential as green reagents and solvents in the synthesis of heterocycles.